SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN TENAGA PENDIDIK TERBAIK MENGGUNAKAN METODE COMPLEX PROPORTIONAL ASSESSMENT - Victor Marudut Mulia Siregar; Kalvin Sinaga; Erwin Sirait; Andi Manalu; Arifin Tua Purba (Politeknik Bisnis Indonesia, 2024)
This research aims to develop and implement a decision support system (DSS) using the Complex Proportional Assessment (COPRAS) method for selecting the best educators at Yayasan Pendidikan Bina Usaha Indonesia (YPBUI). The selection of qualified educators is crucial for creating an effective learning environment, yet the current manual process is prone to bias and inaccuracies. This study involves problem identification, determination of evaluation criteria and weights, data collection on educator performance, and the application of the COPRAS method. The results indicate that the developed DSS provides more objective, transparent, and accurate assessments compared to manual methods. The COPRAS method allows for the proportional integration of various evaluation criteria, resulting in more precise final rankings. The utility calculations show that educators TP04 and TP06 occupy the top positions. With the implementation of this system, YPBUI can enhance performance and service quality in education through a better and more efficient evaluation process.